Hubungan Karakteristik Individu Dengan Perilaku Social Distancing Sebagai Upaya Pencegahan COVID-19 Pada Dewasa Muda di Kota Pekanbaru - Tyagita Widya Sari; Ririn Mayriska (LPPM Universitas Abdurrab, 2023)
Coronavirus Disease 2019 (COVID-19) is a disease that has never been previously identified in humans. The case is increasingly acclaimed on a daily basis around the world, including in Indonesia. At the Riau Province level, 31,397 confirmed cases of COVID-19 have been reported from 12 districts/cities on February 28, 2021 and the Pekanbaru city is the most abundant COVID-19 case report in the Riau province. By the increasing number of cases of COVID-19, World Health Organization (WHO) issued a policy so that people can carry out social distancing, which is a very necessary program to break the chain of COVID-19 transmission. However, some people in Indonesia still consider social distancing as only an ordinary recommendation so there are still many people who do not apply social distancing. Meanwhile social distancing violations are mainly made by a group of young adults who are 18 to 25 years of age. The objective of this study was to determine the correlation of individual characteristics and social distancing behavior as COVID-19 prevention effort on young adults in Pekanbaru City 2021. This research used an analytic observational with a cross sectional study design. This research was conducted on a population of young adults in Pekanbaru City on June 2021. The sampling technique was carried out by cluster sampling with a sample size of 440 respondents. Data analysis was conducted through chi square's test and spearman's correlation test for p-value and coefficient correlation (r). There was a significant correlation between gender (p-value = 0.047) and social distancing behavior. However, there were no significant correlation between education level (p-value = 0.413) and employment status (p-value = 1.000) and social distancing behavior. The individual characteristics which was correlate with social distancing behavior is gender, while education level and employment status have no correlation with social distancing behavior as COVID-19 prevention effort on young adults in Pekanbaru City 2021.